PEMASARAN MADRASAH HUBUNGANNYA DENGAN JUMLAH PESERTA DIDIK BARU - Saepul Maulana; Tatang Ibrahim; Heri Khoiruddin (Jurnal Isema : Islamic Educational Management, 2022)
This study aims to determine whether or not there is a positive and significant relationship between school marketing management and number of new student at Madrasah Tsanawiyah Ar-Rosidiah Cikuda Bandung. This paper using correlation reseach method, this method interpreted as measuring to whether or not relationship between school marketing management as X variable  and number of new student as Y variable. As for the results of the study, it can be concluded that Ar-Rosidiyah's Student Perceptions about school marketing obtained an average value of 3.14. The number was included in the moderate qualification because it was in the 2.5-3.5 interval, the number of new students scored 3.07 with moderate qualification because it was in the interval 2.5-3.5. The results of the calculation of hypothesis testing show t count is 2.07 t table 1.71. Then the level of influence of the variables x and y is 40.5% and has a sufficient correlation. And this shows that there are other factors of 59.5% that influence the student's decision to enter Madrasah Tsanawiyah At-Rosidiyah.